Carbon ion and proton beam irradiation of a normal human TK6 lymphoblastoid cell line within a magnetic field of 1.0 tesla - Yudhistiara, Brian; Weber, Klaus-Josef; Huber, Peter E.; Rühle, Annika; Debus, Jürgen; Hauswald, Henrik (Cancer management and research, 2019)
Background: Considering the increasing simultaneous application of magnetic resonance imaging (MRI) for more precise photon radiotherapy, it will be likely for particle radiotherapy to adopt MRI for future image guiding. It will then be imperative to evaluate the potential biological effects of a magnetic field (MF) on particle irradiation. This study explores such effects on the highly radiosensitive TK6 lymphoblastoid human cell line. Methods: The following three parameters were measured after irradiation with either carbon ion or proton beams using spread out Bragg peaks and applying different doses within a perpendicular 1.0 T MF: (1) cell survival fraction (14 days postirradiation), (2) treatment-specific apoptosis, which was determined through the measurement of population in the sub-G1 phase, and (3) cell cycle progression by means of flow cytometry. These were compared to the same parameters measured without an MF. Results: The clonogenic assay in both treatment groups showed almost identical survival curves with overlapping error bars. The calculated α values with and without an MF were 2.18 (σ=0.245) and 2.17 (σ=0.234) for carbon ions and 1.08 (σ=0.138) and 1.13 (σ=0.0679) for protons, respectively. Similarly, the treatment-specific apoptosis and cell cycle progression showed almost identical curves with overlapping error bars. A two-sample, unpooled t-test analysis was implemented for comparison of all mean values and showed p-values >0.05. Conclusion: No statistically significant difference in biological response of the TK6 cells was observed when they were irradiated using spreadout Bragg peaks within a perpendicular 1.0 T MF as compared to those, which received the same dose without the MF. This should serve as another supporting piece of evidence toward the implementation of MRI in particle radiotherapy, though further research is necessary.